(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article analyzes the importance of the international integration of the higher education system in our country and the problems and solutions of the reforms being carried out in the field of higher education in our country today. In addition, extensive foreign experience in improving the education system and its quality is studied.